Using ultrasonic treated sludge to accelerate pyridine and p-nitrophenol biodegradation. (September 2020) - Lu, Qinyuan; Zhang, Yongming; Li, Naiyu; Tang, Yue; Zhang, Chenyuan; Wang, Wenyi; Zhou, Junqing; Chen, Fu; Rittmann, Bruce E.
Abstract: Aerobic biomass (acclimated activated sludge) was treated by ultrasound and used to accelerate biodegradations of pyridine and p -nitrophenol (PNP), which begin with mono-oxygenation reactions that need an internal electron donor. Ultrasound treatment disrupted the biomass and produced more soluble and (especially) colloidal organic material. Compared with untreated biomass, pyridine- and PNP-biodegradation rates increased when treated biomass provided electron donor. Pyridine- and PNP-biodegradation rates increased by 10% and 20%, respectively, over the control experiments when supernatants from treated biomass were added into the medium. For accelerating pyridine- and PNP removal rates, adding supernatants of treated biomass was equivalent to adding succinate of 0.35 mmol/L and 0.21 mmol/L, respectively. The rates were increased by 63% for both substrates when the entire treated biomass was added. Colloidal solids in the treated biomass contained most of biodegradable electron donor able to stimulate initial monooxygenations of pyridine and PNP. Adding treated biomass together with untreated biomass gave a synergistic impact on enhancing pyridine and PNP biodegradation, because the treated biomass supplied extra donor, while the untreated biomass maintained a high level of active biomass. Graphical abstract: Image 1 Highlights: Ultrasound treatment of biomass produced readily biodegradable electron donor. The extra donor accelerated biodegradation of pyridine and p -nitrophenol. The majority of the produced donor in the treated biomass was colloidal. Mixing treated and untreated biomass had a synergistic impact on the enhancement. The treated biomass provided donor, and the untreated biomass provided active biomass.